External validity of frailty discrimination using the Questionnaire for Medical Checkup of Old-Old-15 and -12 - Tomoyuki Shinohara, Ph.D.; Shota Saito, M.S.; Ayumi Maruyama; Yuta Yabana; Daisuke Higuchi, Ph.D. (Archives of Gerontology and Geriatrics Plus, 2024)
Background: In this study, we aimed to establish the external validity of the cutoff values for frailty identification using both the 15-item and 12-item Questionnaire for Medical Checkups of the Old-Old (QMCOO-15 and QMCOO-12) and the frailty screening index (FSI). Method: This cross-sectional study was conducted in Takasaki, Gunma Prefecture, Japan. Data from 114 participants aged ≥65 years were analyzed. The frailty assessment was based on the Revised Japanese version of the Cardiovascular Health Study (J-CHS) criteria. The QMCOO-15, QMCOO-12, and FSI were also examined. The cutoff value for frailty discrimination using these three scales was set at 3/4. The frailty discrimination performance of the three scales was validated using receiver operating characteristic (ROC) analysis, sensitivity, and specificity. Results: The average age of the participants was 76.4 years, and there were 79 female participants (69.3 %). According to the J-CHS criteria, nine participants (7.9 %) were identified as frail. The areas under the ROC curves were 0.878 for QMCOO-15, 0.853 for QMCOO-12, and 0.912 for FSI. The QMCOO-15 exhibited the highest sensitivity (0.778), whereas the FSI exhibited the highest specificity (0.943). The FSI also achieved the highest accuracy of 0.912. Conclusions: This study revealed the external validity of frailty discrimination using the QMCOO-15, QMCOO-12, and FSI based on the J-CHS frailty assessment criteria. ROC analysis showed that all three tools exhibited good frailty discrimination performance. Hence, we demonstrated the validity of frailty assessments using questionnaires that did not involve physical measurements.